Exploration of Brand Satisfaction on Purchase Decision: Theory of Planned Behavior Perspective - Febrianur Ibnu Fitroh Sukono Putra; Roymon Panjaitan; Elia Resha Fatmawati (Universitas Negeri Malang, 2023)
Brand satisfaction is prominent to bridge purchasing decisions, and it is often linked with perceived value, social media marketing, and brand trust. This study explores the mediating role of brand satisfaction in the relationship between perceived value, social media marketing, brand trust, and purchase decision. The convenience sampling technique was used to collect the data. A self-administered survey from 226 consumers who were sampled in Semarang was involved in this study, and further data was processed using PLS-SEM software. The findings show that perceived value, social media marketing, brand trust, and satisfaction simultaneously have a positive and significant impact on consumer purchasing decisions. The role of brand satisfaction is proven to bridge the relationship between perceived value and the role of social media in purchasing decisions. However, there are negative results related directly or indirectly through brand satisfaction, from brand trust to purchasing decisions. In addition, social media marketing has no impact on brand satisfaction. The findings indicate that brand decisions have yet to become a benchmark for consumers to determine purchasing decisions for shampoo products. The usefulness of this research can trigger product business owners to observe consumer behavior continuously amid fast-moving product innovation competition.Keywords: Perceived value, Purchase decision, Social media marketing, Brand satisfaction, Brand trust